El terror cotidiano en los cuentos de Emilia Pardo Bazán - Bar Cendón, Mónica (Romanica Silesiana)
Most of the literature devoted to Emilia Pardo Bazán places her work in the naturalist school, and despite the gore elements present in it, her oeuvre is not usually interpreted as representative of the horror or the gothic genre. The writer has often expressed her belief that crime is embedded in the daily lives of people, which is manifest in her conviction that “without strange, monstrous and creepy events, we do not know reality.” This article aims to analyze a brief narrative by Pardo Bazán, to address the criminal phenomenon manifest in the author’s newspaper articles. Putting into question the Italian criminology school, where crime is treated as an atavism and a hallmark of our most primitive self, through the projection of violence in its various forms, the writer develops a complicated portrait of the human being (complex, repression or retaliation), which leads us to wonder whether th macabre elements of the narrative are Pardo Bazán’s mirror of reality or the expression of her own ghosts. Key words: Emilia Pardo Bazán, crime, suicide, criminology school, short stories